Epidermodisplasia verruciforme: tratamento combinado com acitretina e interferon alfa-2a Epidermodysplasia verruciformis: combined treatment with acitretin and interferon alpha-2a - Cristiana Silveira Silva; Rodrigo de Oliveira Ramos; Mario Cezar Pires; José Alexandre S. Sittart (Sociedade Brasileira de Dermatologia, 2006)
Comunica-se o resultado do tratamento com acitretina e interferon alfa-2a em doente de 16 anos de idade com epidermodisplasia verruciforme. O diagnóstico foi realizado mediante os achados clínico-histopatológicos e pesquisa in situ positiva para papiloma vírus humano. O quadro clínico era extenso e resistente a outros tratamentos, com risco de desenvolvimento de neoplasias. Houve melhora clínica 30 dias após o início do tratamento, mantida durante os 16 meses de seguimento. We report the result of a treatment with acitretin and alpha-2a interferon in a 16-year-old boy with epidermodysplasia verruciformis. Diagnosis was based on clinical features, histopathological examination and positivity for in situ HPV. The affection was extensive and resistant to other treatment modalities, with a high risk of development of neoplasias. Treatment with oral acitretin associated with subcutaneous recombinant interferon alpha-2a three times per week induced improvement, which was sustained for 16 months of follow-up.